The “double-edged sword” effect of shared leadership on employee voice behavior - Bai, Yina; He, Haoran (Frontiers in Psychology, 2025)
IntroductionThis study investigates the dual-path effects of shared leadership on employee voice behavior through the Empowerment-Servitude Model, with a focus on uncovering the underlying psychological mechanisms. Additionally, it identifies key organizational and individual factors influencing employee voice behavior, offering theoretical insights for strategies aimed at behavioral enhancement.MethodsThis study adopted a multi-method approach, integrating online questionnaires and on-site enterprise visits across two time phases. Data collection yielded 624 valid responses from 13 corporations in Dalian, which were subsequently analyzed statistically.ResultsThe results suggest that, on the one hand, shared leadership, as an empowerment mechanism, positively influences employee voice behaviors through the empowerment pathway associated with organizational status perception. On the other hand, shared leadership, as a depletion mechanism, negatively impacts employee voice behaviors via the servitude pathway, characterized by emotional exhaustion. Employee empowerment expectations play a critical role in triggering these contrasting mechanisms. Specifically, higher levels of employee empowerment expectations mitigate the negative impact of the depletion mechanism while enhancing the positive effects of the empowerment mechanism.DiscussionThis study makes three key contributions to the literature: first, it advances a nuanced understanding of the relationship between shared leadership and employee voice behavior. Second, by examining the moderating role of employee empowerment expectations, it elucidates boundary conditions influencing this relationship. Third, the findings underscore the criticality of empowerment expectations in organizational practice, suggesting that managers implementing shared leadership should systematically assess employees' subjective empowerment expectations, and leverage these expectations to enhance the model's positive effects on voice behaviors.